A real-world pharmacovigilance analysis of adverse events associated with irbesartan using the FAERS and JADER databases - Liu, Qian; Cui, Zhiwei; Deng, Chao; Yang, Chao; Shi, Tao (Frontiers in Pharmacology, 2024)
Abstract Objective: Hypertension is a leading global risk factor for disability and death. Irbesartan, a potent angiotensin II receptor blocker, requires continuous safety monitoring. We conducted a disproportionality analysis of irbesartan-related adverse drug events (ADEs) using the FDA's FAERS and Japan's JADER databases. Methods: We extracted irbesartan-related ADE reports from FAERS (Q1 2004 to Q1 2024) and JADER (Q2 2008 to Q4 2023). We used Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM) for signal detection. Sensitivity analyses were conducted to exclude comorbid medications, and subgroup analyses by age and gender were performed to explore ADE occurrence in specific populations. Th time to onset (TTO) of ADEs was assessed using Weibull distribution test and Kaplan-Meier curves. Results: A total of 5,816 (FAERS) and 366 (JADER) reports were analyzed, with irbesartan-related preferred terms (PTs) involving 27 System Organ Classes (SOCs) in FAERS and 22 in JADER. Three SOCs met detection thresholds in both databases: "metabolism and nutrition disorders," "cardiac disorders," and "renal and urinary disorders." We identified 219 positive signals in FAERS and 20 in JADER, including known signals like hyperkalemia, hypotension, and acute kidney injury. Notably, newly identified signals such as acute pancreatitis (n=50, ROR: 7.76 [5.88-10.25]) and rhabdomyolysis (n=50, ROR: 7.76 [5.88-10.25]) in FAERS and respiratory failure (n=7, ROR: 6.76 [3.20-14.26]) in JADER could have significant clinical implications, as they may lead to severe outcomes if not recognized and managed promptly. Subgroup analyses revealed both similarities and differences in signal detection across gender and age groups. Sensitivity analyses, excluding concomitant medications, confirmed the persistence of key positive signals, including hyperkalemia, angioedema, acute pancreatitis, and agranulocytosis. ADEs mainly occurred within one month (34.14%) and after one year (32.32%) after dosing, with a median onset of 107 days. Conclusion: This study provides valuable real-world evidence on the safety profile of irbesartan. The identification of new safety signals underscores the necessity of updating drug labels, particularly for assessing and managing high-risk patients. Additionally, the TTO analysis emphasizes the importance of sustained vigilance for adverse events over time.